An investigation of abnormal vibration – induced coil spring failure in metro vehicles. (January 2020) - Zhou, Cheng; Chi, Maoru; Wen, Zefeng; Wu, Xingwen; Cai, Wubin; Dai, Liangcheng; Zhang, Heji; Qiu, Weiming; He, Xiang; Li, Maochun
Highlights: An investigation of coil spring failure due to the abnormal vibration. Through the field test, the spring failure is presumed to be caused by the resonance. Given the flexibilities in the track and coil springs, a model was further developed. The results verify the presumes and analyse the influencing factors. Abstract: The coil springs in a number of metro vehicles have been continuously subjected to the failures due to the abnormal vibration in the primary suspension, which imposes highly adverse impacts on the running safety. The field test and simulation of an analytical model were thus performed to identify the causal factors contributing to the abnormal vibrations and failures observed in the metro′s coil springs. The experimental measurements suggested that the coil springs in metro were subjected to the abnormal vibration dominated in the frequency range 55–70 Hz as the vehicle passes the slab track section with fixed sleepers. The dominating frequency of 57 Hz was identified as the bending mode of inner spring via both the hammer test and simulation of a FE-model of coil spring. Given the flexibilities in the track and coil springs, a coupled vehicle/track dynamic model in combination with a flexible coil spring model was further developed for a better understanding of the abnormal vibration observed in the coil spring. The influence of P2 force and corrugation on the inner spring vibration was simulated. The results suggest that the abnormal vibration in the frequency range 55–70 Hz was mainly caused by the resonance of coil spring arising from the P2 force of the slab track with fixed sleepers, and the rail corrugations on this track will aggravate the abnormal vibration.